The complete information literacy ? Unforgetting creation and organisation of information - Isto Huvila (Journal of librarianship and information science, 2011)
Even though the concept of information literacy typically embraces an idea of a complete participation in an information community, its definitions have tended to underline the phases of seeking, searching and evaluation instead of creating information. Shortcomings of information creation can, however, explain many of the difficulties of finding information. This article develops the notion of information literacy with a specific focus on integrating creation and organization of information as central aspects of being information literate and discusses the implications of developing information creation processes from the point of view of information professionals and users. Finally, suggestions are made for how information creation might be improved in practice. Keywords information creation, information literacy, knowledge organization
Keywords: compétences; lecture numérique; recherche d'information